The role of gratitude in enhancing the relationship between doctoral research students and their supervisors. Issue 6 (18th August 2017) - Howells, Kerry; Stafford, Karen; Guijt, Rosanne; Breadmore, Michael
ABSTRACT: While increasing attention is being placed on the crucial importance of a positive supervisor–student relationship, few studies have investigated how to enhance this. Our paper investigates the effect of gratitude practices, proposing it brings both focus and intentionality to the student–supervisor relationship resulting in better research outcomes and, by implication, a positive impact on attrition rates. Recent research has demonstrated that increased attention to gratitude can enhance relational well-being, but only a few studies investigate the role of gratitude in the higher education context. This qualitative case study explores the impact of gratitude as an intervention, following eight Ph.D. students and their two supervisors, in the schools of physical sciences, and medicine over a six-week period of focused attention on practices of gratitude. Findings revealed that all participants noted a positive impact in the areas of communication, social and emotional well-being, as well as on the research process itself.